Mengolah Limbah Cair Tahu Menjadi Biogas Sebagai Bahan Bakar Alternatif Proses Produksi Tahu Dan Peningkatan Kualitas Usaha Di Kelurahan Pela Mampang Jakarta Selatan - Rojali; Desembra Lisa; Indah Restiati; Suparmin (Jurnal Manajemen, Ekonomi, Hukum, Kewirausahaan, Kesehatan, Pendidikan dan Informatika, 2023)
There are quite a number of tofu producers in South Jakarta. However, in its development, business activities that have been carried out for decades have not been able to improve the welfare of the perpetrators. The problems faced include environmental pollution due to the waste produced and weak business management, such as the absence of HPP determination and bookkeeping of business activities. In this regard, community service activities will be carried out with the aim of creating a tofu industry in Pela Sub-District, South Jakarta that is highly competitive and environmentally friendly. Meanwhile, the specific target is to process tofu liquid waste into biogas as an alternative fuel for the tofu production process. The method to be used in achieving these goals is the Participatory Rural Appraisal (PRA) model of participatory community empowerment. This method was chosen based on the consideration that those who have or face problems are partners, therefore the involvement of partners in determining solutions to problems faced and their resolution is very necessary. The method is divided into 3 stages, namely preparation, implementation, and preparation of reports. The preparatory stage begins with counseling about anaerobic tofu wastewater treatment. The next stage is the implementation stage which includes outreach and education activities, demonstration plots, and mentoring. The last stage of this activity is the preparation of progress reports, scientific articles for publication purposes, and the final report. The partners for this empowerment activity are two tofu craftsmen in Pela Mampang Village, South Jakarta. These partners are Small and Medium Industries (IKM), with an average daily production capacity of 250 kg of soybeans and an average annual turnover of Rp. 36,000,000.-.